Credit Analysts’ Decisions on the Information of Entity Survival Uncertainty in Independent Auditors’ Reports - Artie Arditha Rachman; Damayanti Damayanti (Jurnal Ilmiah ESAI, 2012)
The aim of this study was to give empirical findings concerning loan decisions made by bank loan officers when uncertainty aspect is stated in the audit report. The research participants were the bank loan officers in Lampung Province. The findings showed that the bank loan officers’ decisions for disclaimer opinions in assessing the entity’s profitability, assessing the entity’s ability to fulfill his/her debt obligations, and granting a loan to the entity were statistically different from the unqualified opinion unexceptional with explanatory paragraph. Another finding also showed that in disclaimer opinions the loan officers in finding additional information were statistically not different from the unqualified opinion unexceptional with explanatory paragraph. The last finding shows that the bank loan officers in both groups have the same perception about the influence of audit report. In general, this research findings are consistent with those of previous studies.Keywords: decision making, audit report, survival uncertainty, loan officers